A Plea for Internormative Ethics - Robra, Martin (The ecumenical review, 2019)
Plurality of life forms and value systems is a given (almost) everywhere on earth. Imposing on them a value system or individual values and virtues from an exterior position is rather counterproductive. Value systems are normative for individual communities but not the same. They are to relate to each other and to interact, negotiating with each other common goals and the validity and limits of values involved in their relationships and shared action. Anything else leads to tensions and violence. Internormative ethics reflect on such interaction of value systems.